DEVELOPMENT OF INTERACTIVE GAMIFICATION BASED ON THREE-DIMENSIONAL (3D) ANIMATION ON DATA ANALYSIS MATERIAL AND OPPORTUNITIES TO IMPROVE NUMERIC LITERACY OF ELEMENTARY SCHOOL STUDENTS - Asep Zaenudin; Deddy Sofyan; Dadang Jaenudin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to develop and evaluate interactive gamification-based learning media integrated with three-dimensional (3D) animation to improve elementary school students’ numeracy literacy, particularly in data analysis and probability materials. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through tests, questionnaires, observations, interviews, and documentation, involving 32 fifth-grade students. Quantitative data were analyzed using statistical techniques, while qualitative data were analyzed descriptively. The results indicate that the developed learning media is highly feasible based on expert validation, with material validation at 93%, media validation at 94%, and language validation at 91%. The effectiveness of the media is demonstrated by a significant improvement in students’ learning outcomes, with the average score increasing from 48.00% in the pretest to 90.28% in the posttest. Statistical analysis shows a significance value of 0.000 < 0.05 and an N-Gain score of 0.8247 (high category), confirming the effectiveness of the media in enhancing numeracy literacy. Additionally, student and teacher responses were highly positive, indicating increased engagement, motivation, and understanding. In conclusion, the integration of gamification and 3D animation in learning media is effective, engaging, and suitable for improving students’ numeracy literacy in elementary mathematics learning.